Analysis of Marketing Communication Strategies in Increasing Sales and Brand Awareness in Cigarette Companies - Abdillah, Junaidi; Rosdiana Noer, Lissa; Hanoum, Syarifa (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
A cigarette company in Indonesia, referred to as XYZ in this article, is facing declining sales. This study examines the impact of marketing strategies such as advertising, promotions, social media, and sales staff on customer purchasing behavior, specifically sales volume and brand awareness. The study involved a survey of 205 cigarette consumers aged 17 years and above who had previously purchased the XYZ brand. The results of the analysis showed that all marketing strategies used had a positive effect on sales volume and brand awareness. Effective advertising can increase brand awareness among consumers. Sales promotions provide incentives that encourage short-term purchases. Social media is used to interact with consumers and strengthen brand loyalty. Sales staffs play an important role in providing information and building relationships with customers. These findings suggest that XYZ Company can increase sales by implementing a comprehensive marketing approach. By maximizing advertising, promotions, social media, and the role of sales staff, XYZ can strengthen its position in the market. This study provides valuable insights for XYZ management team to develop more effective marketing strategies to overcome declining sales and increase brand awareness among consumers.